PENGARUH LATIHAN FRONT SPLIT TERHADAP EKSTENSI TUNGKAI PADA KLUB BELADIRI KEMPO DOJO RUMBAI PESISIR PEKANBARU - Jani, Rian Ahmad Jani Ahmad; ', Slamet; ', Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem raised in this research is the effect of the training Front Split for Leg Extension self defence kempo club dojo rumbai pesisir pekanbaru . The research aims to determine the effect of Front Split training for Leg Extension self defence kempo club dojo rumbai pesisir pekanbaru.These research is pra experimental, the one group pretest – posttest design. The research was conducted in club dojo rumbai pesisir pekanbaru. The sample of this study of 15 people. Research data collected through the initial pretest and posttest with the Leg Extension test. The data were analyzed descriptive, then further research is done to test the hypothesis that has been asked in the problem, namely : there are Front Split training effect on Leg Extension self defence kempo club dojo rumbai pesisir pekanbaru.Based on t test analysis produces large thitung 16,97 and as much as 1,761 ttabel . Means thitung > ttabel. It can be concluded that Ho denied and H1 accepted. It can be concluded that there is significant effect of the training Front Split (X) and Leg Extension (Y) self defence kempo club dojo rumbai pesisir pekanbaru. Keywords : Front Split, Leg Extension .